Change in Free Radical and Antioxidant Enzyme Levels in the Patients Undergoing Open Heart Surgery with Cardiopulmonary Bypass - Turker, Fevzi Sarper; Dogan, Ayse; Ozan, Gonca; Kibar, Kurtulus; Erisir, Mine (Hindawi Ltd, 2016)
Objective. The purpose of this study is to determine the changes in oxidative damage and antioxidant parameters in open heart surgeries with cardiopulmonary bypass (CPB) in preoperative and early postoperative periods. Methods. Atotal of three consecutive arterial blood samples were obtained from the patients in the study group, in preoperative, early postoperative, and postoperative periods, respectively. Oxidative damage indicator (MDA) and antioxidant indicators (GPx, GSH, CAT, and SOD) were examined. Results. A statistically significant increase was observed in MDA level in postoperative period compared to preoperative and early postoperative periods. GSH levels and CAT activities increased significantly in early postoperative and postoperative periods. Analyses revealed an increase in GPx and SOD enzyme activities only in the postoperative period. Conclusion. Even though the increase in MDA level was suppressed by the increased GSH level and CAT activity like in early postoperative period, efficiency can be brought for the increases in insufficient significant antioxidant parameters in postoperative period by administering antioxidant supplements to the patients and thus the increase in MDA in postoperative period can be significantly suppressed.
Keywords: Postoperative Atrial-Fibrillation; Oxidative Stress; Cardiac-Surgery; Off-Pump; Inflammation; Disease